Towards the automation of in situ experimental phasing. Issue 9 (2nd September 2020) - Liebschner, Dorothee
Abstract : A new approach to in situ experimental phasing introduced by Lawrence et al. (2020, Acta Cryst. D76, 790–801) will be helpful for the macromolecular crystallography community. Abstract : A new approach to in situ experimental phasing introduced by Lawrence et al. (2020, Acta Cryst. D76, 790–801) will be helpful for the macromolecular crystallography community.